Perbandingan Hasil Penilaian Ergonomi pada Industri Polimer Otomotif : Metode Ovako Working Posture Assessment System dan Rapid Entire Body Assessment - Isma Wulansari; Khadijah Sayyidatun Nisa; Abdussalam Topandi; Fauziah Aulia; Bismo Zulfikar Mustofa; Febriza Imansuri; Indra Rizki Pratama (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Work posture plays a crucial role in productivity, and improper postures can lead to ergonomic issues, particularly muscle injuries in workers. The downstream polymer automotive industry, particularly in the production of automotive components using plastic injection processes, often involves workers in various work postures, increasing the risk of muscle injuries. Non-ergonomic work postures can result in muscle tension and health problems, emphasizing the need for a focus on safety and ergonomics in the work environment. This study employed the Ovako Working Posture Assessment System (OWAS) and Rapid Entire Body Assessment (REBA) methods to analyze work postures in the automotive industry. Research recommendations include the necessity for ergonomic control efforts to reduce the impact of muscle injuries due to suboptimal work postures. These ergonomic measures are expected to decrease injury risks, enhance productivity, and contribute to the safety and well-being of workers in the automotive industry. The study provides a foundation for companies to improve efficiency, work quality, and safety conditions in the future.